SPE Annual Fall Technical Conference and Exhibition 1976
DOI: 10.2118/6007-ms
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chemical Treatment Upon Formation Clays is Revealed by Improved SEM Technique

Abstract: American Institute of Mining, Metallurgical, and Petroleum Engineers, Inc. Abstract A number of commonly used stimulation and clay stabilization treatments have been investigated using an improved and more definite Scanning Electron Microscope technique. This technique involves photographing individual groups of clay platelets within a sandstone specimen at high magnification using the Scanning Electron Microscope and then chemically treating the sample. Foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In sandstones, Gdanski and Shuchart (1998) have shown that essentially all clays are unstable in HCl above 149°C. Therefore, other techniques for solving the hightemperature acidizing dilemma have included the borate retardedacid fluid developed by Thomas et al (1976) as well as the use of organic acid/hydrofluoric acid (HF) blends (Van Domelen and Jennings 1995;Shuchart 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In sandstones, Gdanski and Shuchart (1998) have shown that essentially all clays are unstable in HCl above 149°C. Therefore, other techniques for solving the hightemperature acidizing dilemma have included the borate retardedacid fluid developed by Thomas et al (1976) as well as the use of organic acid/hydrofluoric acid (HF) blends (Van Domelen and Jennings 1995;Shuchart 1997).…”
Section: Introductionmentioning
confidence: 99%